Examining Theological and Teleological Intelegence in Shaping the Morality of Islamic Boarding School Students - Ningsih, Wirda (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
This research aims to examine the level of theological and teleological intelligence in the moral development of students at the Al-Kifayah Riau Islamic boarding school. This research uses a quantitative descriptive approach. The entire relevant population is selected for the study as the total sample. There are 24 male students and 32 female students living in the Al-Kifayah Islamic boarding school dormitory in Riau, who are the research subjects. Data were collected through a questionnaire created specifically for this research, which consists of structured questions aimed at gathering information about theological and telelogical intelligence. The results of this research are that the level of theological intelligence of the majority of students is high, while the level of teleological intelligence is moderate.